Good Corporate Governance Memoderasi Pengaruh Corporate Sosial Responsibility dan Penerapan Green Accounting terhadap Kinerja Keuangan - Misutari, Ni Made Somo; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 31 No 12 (2021)DO - 10.24843/EJA.2021.v31.i12.p03, 2021)
The Covid-19 pandemic situation in Indonesia has caused many social responsibility programs that have been planned to be held in 2020 to be delayed. This condition requires companies to design adaptive and innovative CSR programs to respond to the needs of the community. The purpose of this research is to determine the influence of Corporate Social Responsibility (CSR) and the application of green accounting on the company's financial performance and to know the role of Good Corporate Governance (GCG) in strengthening the influence of Corporate Social Responsibility on the company's financial performance. The population in this study are all Green Industry Award-Winning companies listed on the Indonesia Stock Exchange year 2017-2019. The data analysis technique used Moderated Regression Analysis (MRA) with the IBM SPSS Statistics 20 program. The results showed that Corporate Social Responsibility and the interaction of Corporate Social Responsibility with Good Corporate Governance had a positive and significant effect on financial performance. The application of Green accounting has no significant effect on financial performance. The results also show that GCG is a type of all moderation (quasi moderation). Keywords : CSR ; Green Accounting; GCG; Financial Performance.